Contribución al estudio de los procesos estuariales en las desembocaduras de los ríos Rapel y Maipo - Araya Vergara, José F. (Investigaciones Geográficas: Una mirada desde el sur, 2014)
Two surveys to investigate the main physical problems derived from the water movements, the mixing processes and the distribution of salinity and density, weremade in the estuarine environments of the Rapel and Maipo rivers (Chile, 33°55’ and 33°37’ S.). Both bodies of water belong to rivers which drain coastal plain landscapes, but the valley bottoms are not completely covered by the bodies of water. The waters of the Rapel are clear, while those of the Maipo are turbid. The sampling for the Rapel was made in flood of syzygy and for the Maipo, in flood of quadrature, but both cases show sufficient tidal ranges as to suffer tidal influence